A review of approaches and methods in peacebuilding - Gamboa Vesga, Yudy Adriana; Quijano Mejía, Claudia Milena (European Public & Social Innovation Review, 2025)
Introduction: The objective of this work was to critically review the central elements of the theoretical discussion on peacebuilding, including the methodologies proposed for its evaluation and analysis. Methodology: This review was carried out using the method of scoping review or exploratory systematic review, whose purpose is to obtain a panoramic view of the research on a topic, which allows identifying the evolution of knowledge about it, the emerging themes and the main methodological developments used in research in the field. Results: Much of the literature on peacebuilding has dealt with two main themes: first, the critique of the liberal approach in peace studies; second, the perspective that proposes a shift towards the local and its implications. The latter approach attaches great importance to the participation of local communities and advocates bottom-up peacebuilding processes that consider the particularities of each territory. Conclusions: Although there is no consensus on the meaning of peacebuilding and the type of interventions that are considered peacebuilding, it is clear that these are related to other areas of action such as development and the institutional framework. In addition, the multiplicity of interventions, actors and levels involved in peacebuilding makes its measurement difficult.